A TALE OF TWO CITIES - Dickens, Charles, 1812-1870; Orlando, Joe; Evans, George, 1920-2001. (Newbury, Berkshire : CCS Books, 2019)
Dickens's classic story of the French Revolution.
Primary.
Keywords: Dickens, Charles, -- 1812-1870. -- Adaptations; France -- History -- Revolution, 1789-1799 -- Comic books, strips, etc; London (England) -- History -- 18th century; Children's stories -- Comic books, strips, etc; Graphic novels; Comics adaptations